2015
DOI: 10.1177/0022034515612086
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cells and Molecular Networks in Experimentally Induced Pulpitis

Abstract: Dental pulp is a dynamic tissue able to resist external irritation during tooth decay by using immunocompetent cells involved in innate and adaptive responses. To better understand the immune response of pulp toward gram-negative bacteria, we analyzed biological mediators and immunocompetent cells in rat incisor pulp experimentally inflamed by either lipopolysaccharide (LPS) or saline solution (phosphate-buffered saline [PBS]). Untreated teeth were used as control. Expression of pro- and anti-inflammatory cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 40 publications
1
78
0
7
Order By: Relevance
“…It has been reported that when 5 μL of 10 mg mL −1 LPS was injected into rat incisor pulp chamber, inflammatory cell infiltration started 9 h later and the inflammation was limited to the corners of the pulps and disappeared after 3 days (Renard et al . ). Analogously, in previous study no obvious necrosis was observed, but significant vasodilation occurred in the pulp tissues of juvenile and adult rats after 0.5 μg mL −1 LPS injection for 48 h, and IL‐1β expression increased more strongly in adult than in juvenile inflammatory pulp tissues.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…It has been reported that when 5 μL of 10 mg mL −1 LPS was injected into rat incisor pulp chamber, inflammatory cell infiltration started 9 h later and the inflammation was limited to the corners of the pulps and disappeared after 3 days (Renard et al . ). Analogously, in previous study no obvious necrosis was observed, but significant vasodilation occurred in the pulp tissues of juvenile and adult rats after 0.5 μg mL −1 LPS injection for 48 h, and IL‐1β expression increased more strongly in adult than in juvenile inflammatory pulp tissues.…”
Section: Discussionmentioning
confidence: 97%
“…Since they have a stronger healing capacity after injury than mammalian permanent teeth, the dental pulp of rat incisors provides a convenient model for exploring pulp damage repair (Zheng et al 2009). It has been reported that when 5 lL of 10 mg mL À1 LPS was injected into rat incisor pulp chamber, inflammatory cell infiltration started 9 h later and the inflammation was limited to the corners of the pulps and disappeared after 3 days (Renard et al 2016). Analogously, in previous study no obvious necrosis was observed, but significant vasodilation occurred in the pulp tissues of juvenile and adult rats after 0.5 lg mL À1 LPS injection for 48 h, and IL-1b expression increased more strongly in adult than in…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…) and in vivo studies (Renard et al . ) have demonstrated changes in cellular transcription and protein expression when inflamed. Furthermore, cells cultured in mineralizing, angiogenic and neurogenic culture conditions express a range of extracellular molecules, which promote an autocrine and paracrine healing response (Duncan et al .…”
Section: Reviewmentioning
confidence: 99%